NIMG-66. COMPARISON OF STEADY STATE AND DYNAMIC BRAIN METABOLISM BY USING 1H MRSI AND HYPERPOLARIZED [1-13C]PYRUVATE IMAGING IN PATIENTS WITH GLIOMA. (5th November 2018) - Li, Yan; Autry, Adam; Gordon, Jeremy; Crane, Jason; Olson, Beck; Lafontaine, Marisa; Park, Ilwoo; Villanueva-Meyer, Javier; Vigneron, Daniel; Chang, Susan; Nelson, Sarah
Abstract: Proton magnetic resonance spectroscopic imaging (1H MRSI) is a powerful noninvasive method for assessing the spatial extent and properties of abnormal metabolism in patients with glioma. Hyperpolarized 13C metabolic imaging is a new molecular imaging modality that can be used to assess real-time changes in metabolism and has been shown to be safe and feasible in patients with glioma. In this study, both 3D 1H lactate-edited MRSI and hyperpolarized [1-13C]pyruvate imaging data were obtained and compared in thirteen patients with glioma to assess steady state versus dynamic brain metabolism. FLAIR images from the 1H examination were registered to the FSE images from the 13C examination for each subject. The corresponding transformation matrix was then applied to spectra and metabolite maps from the excitation volume of the 1H MRSI data. The volumes of the anatomic and metabolic lesions varied between patients, and using a multi-slice frequency specific EPI sequence allowed improved coverage of the lesion of interest compared to a 2D dynamic EPSI sequence. The choline-to-NAA index values and levels of steady state lactate peak heights from the 1H MRSI data were elevated in the lesion, while 13C bicarbonate levels were reduced and 13C lactate levels were similar or lower compared with normal appearing brain. The initial results indicated that there was a negative association between estimates of hyperpolarized 13C lactate/pyruvate and steady state normalized lactate peak heights, and a positive association between hyperpolarized 13C lactate/pyruvate and Cho/NAA in the T2 lesion. For one patient who received repeated examinations within 2 months and was assessed as having stable disease after treatment, the 13C lactate-to-pyruvate ratio in the T2 lesion was 0.65 vs. 0.35 and 0.43 vs. 0.43 in normal appearing brain. Future studies will evaluate a larger patient population to see whether these relationships hold up.